Medical Humanities in Clinical Rotation of Forensic Medicine and other Clinical Setting - Taufik Suryadi; Kulsum (Britain International for Academic Research (BIAR) Publisher, 2020)
Humanities is one of the pillars of science taught at the Faculty of Medicine. The humanities approach to medicine is believed to be able to provide increased professionalism for doctors in providing services to patients. Several teaching methods have been developed to incorporate medical humanities into the curriculum, including through the approaches of spirituality-religiosity, arts and literature, and narrative medicine. The integration of humanities in medical education can be done by showing professional attitude, communication skills, introspective and practice of self-reflection. In clinical rotation of forensic medicine, medical humanities have been applied to students. One way to implement medical humanities is through several concept approaches, namely religion, bioethics, health law, sociology of medicine and professional behavior.